2015
DOI: 10.12788/jcso.0101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a telehealth intervention on quality of life and symptom distress in patients with head and neck cancer

Abstract: Using telehealth to provide support to patients with head and neck cancer during the acute phase of treatment improved some aspects of posttreatment QoL and symptom burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 38 publications
0
56
0
Order By: Relevance
“…22 A similar effect was found in Pfeifer's (2015) study, as there was no statistically significant difference between groups in the overall QOL score, although there were statistically significant differences in physical wellbeing after the intervention. 27 The Ruland (2013) and Rhyanen (2013) studies reported no statistically significant between-group results for the telehealth intervention on QOL. Both studies did find other statistically significant results related to lower anxiety and depression scale scores for those in the intervention groups compared to the usual care controls over the study period.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…22 A similar effect was found in Pfeifer's (2015) study, as there was no statistically significant difference between groups in the overall QOL score, although there were statistically significant differences in physical wellbeing after the intervention. 27 The Ruland (2013) and Rhyanen (2013) studies reported no statistically significant between-group results for the telehealth intervention on QOL. Both studies did find other statistically significant results related to lower anxiety and depression scale scores for those in the intervention groups compared to the usual care controls over the study period.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…20,25,26 Pfeifer et al (2015) included both breast and prostate cancer patients. 27 Of the nine articles included, only one had statistically significant results for overall QOL scores from baseline to end of the study period and did not have a comparable control group. 20 Two articles did find clinically significant improvements in the intervention effect on QOL, but were not statistically significant.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Similar to our findings, Lubberding and colleagues also found that cancer survivors reported being ill‐prepared to manage symptoms during the posttreatment period and that receipt of personalized advice and tailored supportive care were identified as desirable interventions. Two recent studies evaluated the efficacy of using proactive automated telephone‐based monitoring of symptoms to improve symptom management at home during cancer treatment and were found to improve uncontrolled symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies evaluated the efficacy of using proactive automated telephone-based monitoring of symptoms to improve symptom management at home during cancer treatment and were found to improve uncontrolled symptoms. 24,25 This is the first study to our knowledge that explored patient perspectives about which components of DS would be desirable for enhancing communication with clinicians. Previous studies have focused on examining the usability or efficacy of eHealth systems.…”
Section: Discussionmentioning
confidence: 99%
“…The BT Telehealth service, operated by British Telecommunications plc in the UK, enables patients to receive proactive care and facilitates greater patient involvement, which can reduce the unplanned use of health resources and thus the related costs to the National Health Service (Cruz et al 2014). Basic telehealth technology enables patients to improve QoL and better manage symptoms during head and neck cancer treatment (Pfeifer et al 2015). Measuring and improving the wellbeing of the population is a means of assessing the progress of a society, and thus should be a focus of governments (WHO 2012).…”
Section: Introductionmentioning
confidence: 99%